Exploring the impact of a conceptual model on students’ reflective skills development: a case study of Kazakhstan - Venera Mussina; Saltanat Abildina; Kamalbek Berkimbayev; Zhanna Zhussupova; Berikzhan Almukhambetov (International Journal of Evaluation and Research in Education (IJERE), 2026)
The growing interest in reflection and the development of reflective skills (RS) among future teachers is linked to a shift in Kazakhstan’s educational paradigm. Reflective thinking is recognized as an effective means of analyzing everyday practice, introducing students to key aspects of their profession, and encouraging lifelong learning. However, a paradox exists in the professional training system: although students’ RS are considered professionally essential, insufficient attention is given to their systematic development. This study aimed to examine the impact of a conceptual model (CM) on fostering students’ RS. A quasi-experimental design was employed with 120 participants. The experimental group (EG) demonstrated significantly higher levels of RS compared to the control group (CG) (p<0.05). The dynamic changes in students’ RS observed during the learning process indicate the strong pedagogical potential of the proposed model. The findings show that teachers perceive the use of the CM as an effective tool for enhancing students’ RS. It was also found that the model increases students’ interest in the learning process and contributes to the development of RS. Overall, the study supports the effectiveness of using a CM to enhance RS, thereby contributing to the professional readiness of future primary school teachers.